Nanoparticle surfactants as a route to bicontinuous block copolymer morphologies - Kim, Bumjoon J (Langmuir : the ACS journal of surfaces and colloids, 2007)
The surface chemistry of nanoparticles can be modified so that these particles behave like surfactants and localize at interfaces between two fluids. We demonstrate that small volume fractions phi(P) of such surfactant nanoparticles added to lamellar diblock copolymers lead initially to a decrease in lamellar thickness with phi(P), a consequence of decreasing interfacial tension, up to a critical value of phi(P), beyond which the block copolymer adopts a bicontinuous morphology. These bicontinuous morphologies have stable domain spacings below 100 nm that further decrease with increasing phi(P) and offer new routes to nanoscopically engineered polymer films with potential photovoltaic, fuel cell, and battery applications